2018
DOI: 10.1155/2018/2419183
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Semen Ziziphi Spinosae Exerts Anxiolytic Effects during Nicotine Withdrawal via Improvement of Amygdaloid CRF/CRF1R Signaling

Abstract: Anxiety during nicotine withdrawal (NicW) is a key risk factor for smoking relapse. Semen Ziziphi Spinosae (SZS), which is a prototypical hypnotic-sedative herb in Oriental medicine, has been clinically used to treat insomnia and general anxiety disorders for thousands of years. Thus, the present study evaluated the effects of the aqueous extract of SZS (AESZS) on NicW-induced anxiety in male rats that received subcutaneous administrations of nicotine (Nic) (0.4 mg/kg, twice a day) for 7 d followed by 4 d of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…spinosa (Bunge) Hu ex H. F. Chou, is a well‐known traditional Chinese medicine that has been used to treat anxiety and insomnia for thousands of years in China . Modern pharmacological research shows that the extract of ZS possesses many kinds of biological activities including a sedative‐hypnotic effect , an antidepressant effect , an anxiolytic effect , and so on. These bioactivities are mainly attributed to the rich active components in ZS, especially flavonoids, saponins, and alkaloids .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…spinosa (Bunge) Hu ex H. F. Chou, is a well‐known traditional Chinese medicine that has been used to treat anxiety and insomnia for thousands of years in China . Modern pharmacological research shows that the extract of ZS possesses many kinds of biological activities including a sedative‐hypnotic effect , an antidepressant effect , an anxiolytic effect , and so on. These bioactivities are mainly attributed to the rich active components in ZS, especially flavonoids, saponins, and alkaloids .…”
Section: Introductionmentioning
confidence: 99%
“…sedative-hypnotic effect [3], an antidepressant effect [4], an anxiolytic effect [5], and so on. These bioactivities are mainly attributed to the rich active components in ZS, especially flavonoids, saponins, and alkaloids [6].…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawal from repeated use of NIC in rodents produces substantial anxiety-like behaviors in various instrumental tests, including the EPM test; these tests have been validated in previous studies in our laboratory and by other groups [12,29]. As expected, in the present study, the ethological phenotype of anxiety was observed in the EPM test in that the NIC withdrawal rats exhibited decreased numbers of entries into open arms and spent less time in the open arms of the EPM compared to saline-treated controls.…”
Section: Discussionmentioning
confidence: 79%
“…At 30 min after the final dose of ISL, the rats were checked in the EPM to assess anxiety-like behaviors, as described previously [12]. Briefly, the EPM was comprised of two open arms (50 cm long × 10 cm wide) and two closed arms (enclosed by dark acrylic walls 40 cm high), which were elevated above the floor to a height of 50 cm, and monitored with a video-tracking system (Shanghai Xinruan Technology Co., Shanghai, China).…”
Section: Epm Testmentioning
confidence: 99%
See 1 more Smart Citation